Impact of a 3-year multi-centre community-based intervention on risk factors for chronic disease and obesity among free-living adults: the Healthy Alberta Communities study. (December 2016) - Lytvyak, Ellina; Olstad, Dana; Schopflocher, Donald; Plotnikoff, Ronald; Storey, Kate; Nykiforuk, Candace; Raine, Kim
Abstract Background Healthy Alberta Communities (HAC) was a 3-year community-based intervention to reduce lifestyle-related risk factors for chronic disease and obesity at a population-level. The current paper examines changes in blood pressure (BP) and anthropometric indicators within HAC communities compared to secular trends. Methods Between 2006 and 2009, this community-academic partnership sought to create environments supportive of healthier dietary and physical activity behaviours within four diverse communities in Alberta, Canada. Height, weight, waist and hip circumference and BP were measured among 1554 and 1808 community residents at baseline (2006) and follow-up (2009), respectively. A comparison sample was drawn from a representative national survey. Samples were stratified by age and change between pre- and post-intervention was assessed using t-tests. Changes in parameters over time between groups were compared using meta-analysis. The net difference in change in outcomes (change in intervention communities minus change in comparison group) represented the effect of the intervention. Results Adjusted systolic (SBP) and diastolic (DBP) BP declined within most age groups in HAC communities from pre- to post-intervention. The net decline in SBP was 1 mmHg in 20–39 year olds (p = 0.006) and 2 mmHg in 40–59 year olds (p = 0.001), while the net decline in DBP was 3 mmHg in 20–39 year olds (p < 0.001), 2 mmHg in 40–59 year olds (p < 0.001) and 3 mmHg in 60–79 year olds (p < 0.001). The net increase in the proportion of individuals with normal BP was 5.9 % (p < 0.001), while the net decline in the proportion of individuals with stage 1 hypertension was 4.5 % (p < 0.001). BMI and body weight were unchanged. There was a significant net increase in waist and hip circumference among 20–39 year olds within intervention communities. Conclusions Findings suggest HAC succeeded in shifting the population distribution of BP in a leftward direction. By contrast, anthropometric parameters remained unchanged or worsened within intervention communities. Therefore, while improvements in some clinical risk factors can be achieved through relatively diffuse and shorter-term community-level environmental changes, improvements in others may require interventions of greater intensity and duration. Evaluating the success of community-based interventions based on their efficacy in changing individual-level clinical indicators may, however, underestimate their potential.